Quality of Life in Patients with Chronic Oral Mucosal Conditions: A Qualitative Research - Amir Reza Gandjalikhan Nassab; Nader Navabi; Maryam Mohammad Pour; Negar Charrosta; Maryam Alsadat Hashemipour (Association of Support to Oral Health Research (APESB), 2021)
Objective: To use qualitative research methods to evaluate the experiences of patients with chronic oral diseases. Material and Methods: Purposive sampling was used to recruit patients from the Oral Medicine Unit of Kerman University Dental School. An experienced independent facilitator convened the focus groups and conducted individual interviews in a non-clinical setting. Focus groups were mixed regarding their gender, age, chronic oral mucosal condition, time since diagnosis, and severity. A total of 39 patients participated in the study, including patients with oral lichen planus, pemphigus, recurrent aphthous stomatitis and leukoplakia. Results: Analysis of the interviews revealed that patient views could be divided into the following themes: biopsychosocial issues, treatment limitations and side effects, unpredictability of the conditions and the potential for malignant transformation. Chronic oral mucosal conditions affected patients' daily lives in various areas, from physical health and functioning to concerns about their future. Conclusion: The oral medicine practitioner's role in treating patients with chronic oral mucosal diseases extended beyond active management and symptomatic relief to the management of all aspects of these conditions that affected their daily lives.